Harmonizing Security Rights and Bankruptcy Law: A Systematic Review of Global - Sanusi (ASIAN PUBLISHER, 2024)
Conflict between security rights and bankruptcy law is a crucial issue, especially in the context of cross-border transactions. This suggests that harmonization of security rights and bankruptcy law is essential to understand. This study aims to provide a systematic analysis of the regulation of security rights and bankruptcy law across jurisdictions through a systematic literature review using the PRISMA methodology and the VOSviewer bibliometric tool. The findings of this study indicate significant regulatory inconsistencies across jurisdictions, particularly in balancing creditor priorities and distributive justice in bankruptcy proceedings. Empirical data suggests that while frameworks such as the UNCITRAL Model Law offer potential solutions, their adoption and implementation remain fragmented, especially in developing countries. This study underscores the importance of creating unified international standards to enhance legal certainty, optimize asset recovery, and promote inclusive and adaptive regulatory reforms.